An empirical study on transit-oriented low-carbon urban land use planning: Exploratory Spatial Data Analysis (ESDA) on Shanghai, China. (April 2016) - Dou, Yi; Luo, Xiao; Dong, Liang; Wu, Chuntao; Liang, Hanwei; Ren, Jingzheng
Abstract: Low-carbon urban development is a hot spot of global concerns for fighting against climate change for China, transportation sector has a significant contribution to urban CO2 emissions, while the emissions are still increasing. Transit-Oriented Development (TOD) strategies provide a novel approach for urban planners to facilitate the urban carbon mitigation from transportation sector in long-term. While TOD strategies are emerging cases, they are merely qualitatively discussed in China, lacking practical indicators and quantitative verification for supporting the real urban plan. With such circumstance, this study aims to conduct an empirical and quantitative study on the applications of TOD strategy in Shanghai based on Exploratory Spatial Data Analysis (ESDA) and the updating data. Firstly, the changes of urban morphology were quantitatively analyzed by spatial cluster analysis, which reveals the layer structure changes and residents migration at about 1 km accuracy. Secondly, accessibility was selected as an indicator for urban transportation and estimated by method based on Time Cost Weighted Distance. Finally, the effectiveness of TOD was investigated by evaluating the integration between population and transportation accessibility with Geographic Weighted Regression model. Results highlight that TOD can effectively improve the transportation network with higher accessibility and lower urban carbon emissions. The outcomes of this study provide critical insights to the recent practice in Shanghai, as well as the practical guidance to low carbon urban planning in developing countries.